Comparative transcriptomic analysis and functional characterization reveals that the class III peroxidase gene TaPRX-2A regulates drought stress tolerance in transgenic wheat - Su, Peisen; Sui, Chao; Niu, Yufei; Li, Jingyu; Wang, Shuhan; Sun, Fanting; Yan, Jun; Guo, Shangjing (Frontiers in Plant Science, 2023)
Drought is a major abiotic stress that reduces crop yields and quality worldwide. Although some genes involved in the response to drought stress have been identified, a more in-depth understanding of the mechanisms underlying wheat tolerance to drought is needed for the control of drought tolerance. Here, we evaluated the drought tolerance of 15 wheat cultivars and measured their physiological–biochemical parameters. Our data showed that the drought tolerance of the resistant wheat cultivars was significantly higher than that of drought-sensitive cultivars, which was associated with a greater antioxidant capacity of the former. Transcriptomic analysis revealed that different mechanisms of drought tolerance exist between the wheat cultivars Ziyou 5 and Liangxing 66. Transcriptomic analysis also revealed a large number of DEGs, including those involved in flavonoid biosynthesis, phytohormone signalling, phenolamides and antioxidants. qRT–PCR was performed, and the results showed that the expression levels of TaPRX-2A were significantly different among the various wheat cultivars under drought stress. Further study revealed that overexpression of TaPRX-2A enhanced tolerance to drought stress through the maintenance of increased antioxidase activities and reductions in ROS contents. Overexpression of TaPRX-2A also increased the expression levels of stress-related genes and ABA-related genes. Taken together, our findings show that flavonoids, phytohormones, phenolamides and antioxidants are involved in the plant response to drought stress and that TaPRX-2A is a positive regulator of this response. Our study provides insights into tolerance mechanisms and highlights the potential of TaPRX-2A overexpression in enhancing drought tolerance in crop improvement programmes.